Effects of Angiotensin-Converting Enzyme Inhibitory Peptide LAP on Vascular Remodeling. (October 2013) - Huang, Junling; Luo, Ming; Fang, Hong; Zheng, Huan; Shen, Yi; Li, Lingxia; Deng, Yuqing; Xu, Huifeng
<x xml:space="preserve">Abstract</x> The aim of this article is to study the efficiency of an angiotensin-converting enzyme (ACE)-inhibitory peptide LAP on the blood pressure (BP) and the vascular remodeling in spontaneously hypertensive rats (SHRs). Ten-week-old male SHRs were divided into four groups with 10 animals in each group and treated for 2 months: blank, pseudo-experimental (NS), enalapril (ENA), and LAP. The alterations of BP, plasma angiotensin II (AngII) levels, and morphological changes of left common carotid artery and the third level of superior mesenteric artery were investigated. After 2 weeks of treatment, LAP and ENA significantly decreased BP and the antihypertensive effects lasted till the end of experiment. After 2 months, LAP and ENA also significantly lowered plasma AngII levels. LAP and enalapril significantly lowered vascular medial thickness, media thickness/lumen diameter, medial cross-sectional area, and mean nuclear area of smooth muscle cells in left common carotid artery. When compared to the blank group, LAP and ENA significantly lowered the percentages of collagen fibers in the vascular area of left common carotid artery with 24.84 ± 0.53, 23.36 ± 0.99 versus 31.82 ± 0.57 (blank), respectively, and those of the third level of superior mesenteric artery with 15.82 ± 0.60, 15.15 ± 0.71 versus 23.42 ± 0.72, respectively. LAP had a beneficial effect on BP and vascular remodeling in SHRs. These findings suggest the potential therapeutic value of LAP in the treatment of hypertension.